The process of retinal vascularization in retinopathy of prematurity after ranibizumab treatment in China - Meng, Qing-Yu (Int J Ophthalmol, 2019)
AIM: To explore the process of retinal vascularization and risk factors for retinopathy of prematurity (ROP) treated with intravitreal ranibizumab (IVR) as monotherapy. METHODS: Infants with type 1 ROP who received IVR as primary treatment from August 2014 to October 2016 at Peking University People's Hospital's Ophthalmology Department were included in the study. All eyes received 0.25 mg ranibizumab at initial treatment. Retinal vascularization was evaluated clinically. Potential risk factors were also recorded and examined. RESULTS: Retinal vascularization was completed in 126 eyes (62.7%), and retinal vascularization terminated in zone II and zone III with 16 eyes (7.9%) and 44 eyes (21.9%), respectively, after more than 1-year follow-up. In multivariate regression analysis, lower birth weight (BW), severity of ROP and repeated injections were found to be risk factors for peripheral avascular area (P<0.05). CONCLUSION: In our retrospective study, 29.8% of the ROP eyes treated with ranibizumab have peripheral avascular area at the last follow-up. Lighter BW and the severity of ROP are risk factors. Furthermore, repeated injections also increase the risk of retinal peripheral avascular area remaining in ROP patients.